2011
DOI: 10.4103/0972-124x.92580
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between scalpel technique and electrosurgery for depigmentation: A case series

Abstract: A beautiful smile definitely enhances the personality of an individual and reveals self-confidence. The harmony of the smile is determined not only by the shape, position, and color of the teeth but also by the gingival tissues. Gingival pigmentation results from melanin granules which are produced by melanoblasts. Although melanin pigmentation of the gingiva is a completely benign condition and does not pose any medical problem, complaints of “black gums” are common particularly in patients having a very high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…This study is a first of its kind to evaluate pain levels using the VAS to compare electrosurgery and diode lasers for gingival depigmentation, although there are some studies that compared the scalpel technique and electrosurgery. [ 22 23 ] Kaarthikeyan et al . [ 24 ] assessed pain using a VAS in patients undergoing gingival depigmentation by the scalpel technique and 970-nm diode laser surgery and found a statistically significant difference between the levels of pain, with the laser group demonstrating lesser pain intraoperatively compared with the scalpel group.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a first of its kind to evaluate pain levels using the VAS to compare electrosurgery and diode lasers for gingival depigmentation, although there are some studies that compared the scalpel technique and electrosurgery. [ 22 23 ] Kaarthikeyan et al . [ 24 ] assessed pain using a VAS in patients undergoing gingival depigmentation by the scalpel technique and 970-nm diode laser surgery and found a statistically significant difference between the levels of pain, with the laser group demonstrating lesser pain intraoperatively compared with the scalpel group.…”
Section: Discussionmentioning
confidence: 99%
“…Although several techniques are currently in use, the scalpel technique is still the most widely employed as it is most economical compared to other techniques, which require more advanced armamentarium and is therefore highly recommended in consideration of the equipment constraints in developing countries. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Earlier studies have shown no significant difference in the density of distribution of melanocytes between light-skinned, dark skinned and black individuals. [ 4 ] However, melanocytes of dark skinned and black individuals are uniformly highly reactive, in light-skinned individuals, melanocytes are highly variable in reactivity. [ 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…An esthetic smile does not only create an impact on the viewers but it also enhances the personality and self-confidence of the individual. [1] Various factors contribute to the composition of an esthetic smile such as shape, color, and position of teeth and gingiva. [1] Of these, the color of gingiva plays a significant role in the overall smile esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Various factors contribute to the composition of an esthetic smile such as shape, color, and position of teeth and gingiva. [1] Of these, the color of gingiva plays a significant role in the overall smile esthetics. [1] The color of gingiva is affected by some factors, including the thickness of the epithelium, the degree of keratinization, size of blood vessels, and color pigments within the epithelium.…”
Section: Introductionmentioning
confidence: 99%